EFFECT OF EYE FISHING SIZE ON RESULTS OF FISHING FISH CATCHES IN PPI KAMBANG PESISIR SELATAN WEST SUMATERA - Adzandi, Facjri Restu; Brown, Arthur; Usman, Usman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractThe study was conducted on September 19 - September 28 2019 in the waters of Kambang, Lengayang Subdistrict, Pesisir Selatan Regency, West Sumatra.The method used in this research is experimental fishing method. The purpose of this study is to determine the effect of using different sizes of fishing lines on the catch of fishing lines. Catches obtained during the 10-day study(10 fishing trips)By using the fishing line, there are as many as 112 fish weighing 36.5 kg. Where the number of catches based on the size of the hook 6 as many as 19 tails weighing 7.27 kg, fishing rod size 13 as many as 67 fish weighing 21.67 kg, and the size of fishing rod 14 as many as 26 with a weight of 7,595 kg. Keyword:influence of hooks, hand line, catch